The effect of financial inclusion, exchange and interest rates on inflation in 17 emerging market countries - Herlina, Deswita; Suci, Stannia Cahaya; Prastuti, Rizky Hanifah (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
Financial inclusion is the ability of individuals or groups to have access to products and services. Services are the ability to meet the needs of activities, such as transactions, payments, savings, credit and insurance, responsibly and sustainably. The study aims to analyze the impact of financial inclusion, exchange rates and interest rates on inflation in 17 emerging markets from 2008 to 2021. This study uses the Index of Financial Inclusion (IFI) and the System Generalized Method of Moment. (Sys-GMM). Research findings show that financial inclusion has a significant negative impact on inflation, while exchange rates and interest rates have a positive impact on the inflation of 17 emerging markets. As financial inclusion rises, then inflation will decrease. Financial inclusion can increase the effectiveness of monetary policy that then affects inflation.